Development of an equation to screen for solar hemorrhages from digital cushion ultrasound texture analysis in veal calves at slaughter - Fabbri, Giorgia; Magrin, Luisa; Gottardo, Flaviana; Armato, Leonardo; Contiero, Barbara; Gianesella, Matteo; Fiore, Enrico (Frontiers in Veterinary Science, 2022)
Claw disorders are a relevant welfare issue in the cattle industry, fast and accurate diagnoses are essential for successful treatment and prevention. The aim of the present study was to develop an equation to assess the presence of solar hemorrhages from real-time ultrasound images texture analysis at slaughter. Eighty-eight hind feet were collected at the slaughterhouse from 44 Holstein male veal calves. The claws were trimmed by a veterinarian hoof-trimmer, approximately 30 minutes after the calves’ slaughter, and classified into healthy and affected by solar hemorrhages. At the same time, ultrasound images were collected for each claw. Sole soft tissues’ thickness was measured, and texture analysis was performed using MaZda software. The resulting parameters from sole soft tissues’ measurements and texture analysis were screened with a stepwise linear discriminant analysis using the absence or presence (0/1) of solar hemorrhages as the dependent variable. Results from the stepwise analysis identified 9 variables (among 279) as predictors, and an equation was developed and used to predict the presence or absence of solar hemorrhages on the scanned claws by binary measure: values ≤ 0.5 counted as 0, while those > 0.5 as 1. Validation of the equation was performed testing predicted lesions (LESpred) against the clinically evaluated lesions (LESeval) with a confusion matrix, a ROC analysis, and a Precision Recall curve. Results of the present study suggest that the equation proposed has a good potential for detecting effectively hemorrhages of the sole by ultrasound imaging texture means, and could be used to monitor unsatisfactory housing and management conditions at the farm level, and for early management intervention and prevention.